Management and outcomes of spontaneous coronary artery dissection: a systematic review of the literature - Petrović, Milovan; Miljković, Tatjana; Ilić, Aleksandra; Kovačević, Mila; Čanković, Milenko; Dabović, Dragana; Stojšić Milosavljević, Anastazija; Čemerlić Maksimović, Snežana; Jaraković, Milana; Andrić, Dragica; Golubović, Miodrag; Bjelobrk, Marija; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background: Contemporary management of spontaneous coronary artery dissection (SCAD) is still controversial. This systematic review of literature aims to explore outcomes in the patients treated with conservative management versus invasive strategy. Methods: The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed when we extensively searched three electronic databases: PubMed, ScienceDirect, and Web of Science for studies that compared conservative versus invasive revascularization treatment outcomes for SCAD patients from 2003 to 2023. The outcomes of interest were all-cause death, major adverse cardiovascular events (MACE): acute coronary syndrome (ACS), heart failure (HF), need for additional revascularization, target vessel revascularization (TVR), SCAD recurrence, and stroke. Results: Systematic review included 13 observational studies evaluating 1801 SCAD individuals. The overall mean age was 49.12 +/-3.41, with 88% of females. The overall prevalence of arterial hypertension was 33.2%, hyperlipidemia 26.9%, smoking 17.8%, and diabetes 3.9%. Patients were diagnosed with Non-ST elevated myocardial infarction (NSTEMI) in 48.5%, ST elevated myocardial infarction (STEMI) in 36.8%, unstable angina in 3.41%, stable angina in 0.56%, and 0.11% were diagnosed with various types of arrhythmias. The left anterior descending artery (LAD) was the most common culprit lesion in 51%. There were initially 65.2% of conservatively treated patients versus 33.4% that underwent PCI or CABG 1.28%. SCAD-PCI revascularization was associated with a variable range of PCI failure. The most common complications were hematoma extension and iatrogenic dissection. SCAD PCI revascularization frequently required three or more stents and had residual areas of dissection. Overall reported in-hospital and follow-up mortality was 1.2% and 1.3%, respectively. The follow-up range across studies was 7.3-75.6 months. Authors reported variable prevalence of MACE, recurrent SCAD up to 31%, ACS up to 27.4%, TVR up to 30%, repeat revascularization up to 14.7%, UA up to 13.3%, HF up to 17.4%, and stroke up to 3%. Conclusion: Our results highlight that conservative treatment should be the preferred method of treatment in patients with SCAD. PCI revascularization is associated with a high prevalence of periprocedural complications. SCAD poses a considerable risk of MACE, mainly associated with TVR, ACS, and recurrent SCAD.